2015
DOI: 10.1109/mcom.2015.7263347
|View full text |Cite
|
Sign up to set email alerts
|

A low-cost desktop software defined radio design environment using MATLAB, simulink, and the RTL-SDR

Abstract: In the last 5 years, the availability of powerful DSP and Communications design software, and the emergence of relatively affordable devices that receive and digitize RF signals, has brought Software Defined Radio (SDR) to the desktops of many communications engineers. However, the more recent availability of very low cost SDR devices such as the RTL-SDR, costing less than $20, brings SDR to the home desktop of undergraduate and graduate students, as well as both professional engineers and the maker communitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
107
0
12

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(119 citation statements)
references
References 8 publications
0
107
0
12
Order By: Relevance
“…The PECAS receiver is based on RTL-SDR [23]. RTL-SDR is a very low cost Software Defined Radio (SDR) that employs a DVB-T TV tuner dongle based on the Realtek RTL2832U chipset.…”
Section: A Hardwarementioning
confidence: 99%
“…The PECAS receiver is based on RTL-SDR [23]. RTL-SDR is a very low cost Software Defined Radio (SDR) that employs a DVB-T TV tuner dongle based on the Realtek RTL2832U chipset.…”
Section: A Hardwarementioning
confidence: 99%
“…Combining the GNU Radio and USRP in [8] an SDR based wireless system was developed. Work recently published by a team at the University of Strathclyde [9] has shown how the RTL-SDR can be used to perform automated sweeps of the RF spectrum; opening the possibility of using this device to detect PD signals. No previous research was found regarding PD detection using RTL-SDR devices.…”
Section: Related Workmentioning
confidence: 99%
“…Very popular and known packages as GNU-Radio [4], LabVIEW [5], MATLAB [6], all of them with RTL-SDR support, have been tested for our objective, but we finally propose to use PothoSDR [7] and SDR# [8], which is what the authors are using in the classroom. Alternatives like MATLAB or LabVIEW were discarded due high licensing cost and GNU-Radio was dropped because it needs a working Linux platform.…”
Section: Sdr Softwarementioning
confidence: 99%